Distinct temporal requirements for Runx1 in hematopoietic progenitors and stem cells - Tober, Joanna (Company of Biologists, 2013)
The transcription factor Runx1 is essential for the formation of yolk sac-derived erythroid/myeloid progenitors (EMPs) and hematopoietic stem cells (HSCs) from hemogenic endothelium during embryogenesis. However, long-term repopulating HSCs (LT-HSCs) persist when Runx1 is conditionally deleted in fetal liver cells, demonstrating that the requirement for Runx1 changes over time. To define more precisely when Runx1 transitions from an essential factor to a homeostatic regulator of EMPs and HSCs, and whether that transition requires fetal liver colonization, we performed conditional, timed deletions of Runx1 between E7.5 and E13.5. We determined that Runx1 loss reduces the formation or function of EMPs up through E10.5. The Runx1 requirement in HSCs ends later, as deletion up to E11.5 eliminates HSCs. At E11.5, there is an abrupt transition to Runx1 independence in at least a subset of HSCs that does not require fetal liver colonization. The transition to Runx1 independence in EMPs is not mediated by other core binding factors (Runx2 and/or Runx3); however, deleting the common non-DNA-binding β subunit (CBFβ) severely compromises LT-HSC function. Hence, the requirements for Runx1 in EMP and HSC formation are temporally distinct, and LT-HSC function is highly reliant on continued core binding factor activity.